The impact of the COVID-19 pandemic on the use of Emergency Departments in Italy - Sanmarchi, F.; Golinelli, D.; Lenzi, J.; Grilli, R.; Fantini, M. P.; Gori, D. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. During 2020, COVID-19 had a diversified distribution in Italy, the first nation in Europe to experience the outbreak of the epidemic. This was linked to geographical differences in population density and distribution of healthcare facilities, including Emergency Departments (EDs). This study aims to assess the impact of the pandemic on ED utilization in 2020 across different subpopulations and geographical locations in Italy. Methods. We used anonymized data from a survey conducted by the Italian National Institute of Statistics on 25,000 families to analyze the yearly rate of people who used EDs from 2015 to 2020. The rate of persons who accessed ED services in 2020 per 1,000 population was compared with those of the previous non-pandemic years. Results. The number of people accessing EDs in 2020 was 32.3% lower, although this reduction was not uniform across the 21 regions / autonomous provinces. People aged 0–14 years experienced the highest reduction in ED visits. In 2020, low educational level people exhibited a steeper reduction in the use of EDs. Conclusions. This study shows a significant drop in EDs use especially by children; the population section mostly affected by the effects of the pandemic. This study also confirms that education and socio-economic status are important determinants of ED use. The heterogeneous reduction in ED use across the regions of Italy highlights the need to further investigate the impact of this pattern on the health of the population, as well as to define adequate preparedness strategies to face future emergencies.